Narrative Cycles in Icons and Illustrated Manuscripts of the 16th – Early 17th Centuries: On the Problem of Compositional Organization - Aitova, Sofia N. (Actual Problems of Theory and History of Art, 2023)
The paper considers the metamorphosis in the composition of the narrative cycles of late medieval Russian icons in the context of the same tendencies in illustrated manuscripts. We observe a number of new trends in iconography of that period: the complication of the narrative cycle in the traditional type of hagiographic icons (e.g., the arrangement of several narrative episodes in one kleimo), an increase in the number of scenes and characters to strengthen and supercharge the symbolic idea, and the expansion of iconographically standard scenes into narrative cycles (e.g., the icons of the Nativity of Christ with an expanded composition). It is important to define the place of the illuminated manuscripts of the 16th century in the processes of innovation of illumination principles (examples: the illustrated miscellany of Chudov monastery (Egorov’s miscellany) of the 1560–1570s, RSL, F. 98, no. 1844, the illustrated Hagiography of Sergius of Radonezh of the late 16th century, RSL, F. 304/III, no. 21). Trying to make a methodological research of this problem, it is tempting to explain the changes in the composition of narrative cycles in icons by the influence of illuminated manuscripts. However, we propose to analyze these two types of visual art as two independent forms, even though they have some common aspects within our research. It is more a question of assimilating the principles inherent to another form of painting in order to express the certain nuances of an image, rather than an influence of one on the other.